Juridical Analysis of Legal Updates on Crypto Assets in Indonesia (Comparative Study of Indonesian Law with Singapore and Islamic Law Views) - Fitriana, Wulan; Maiza Dea Nuraini (Journal of Transcendental Law, 2023)
The progress of the financial industry marked by the emergence of crypto assets at the global level is a result of the development of technological advances, through Regulation No. 99 of 2018 concerning the General Policy for the Implementation of Crypto Asset Trading and followed up with regulation of the Commodity Futures Trading Supervisory Agency No. 8/2021 making crypto assets recognized as commodities, meaning that crypto assets in Indonesia are only recognized as commodity assets not as means of payment, related to the development plan of crypto asset exchanges in Indonesia, the need for legal updates related to regulations, human resources and governance. Besides, given its fluctuating nature and tending to give discontent, its use as a transaction is forbidden in Islam, but is lawful as long as it is used as a commodity asset with clear underlying assets and fulfills the sil’ah.This type of research is normative juridical and is analyzed using qualitative data analysis, using legal comparisons from countries that already have crypto asset regulation first, then the Singapore state deserves to be used as a parameter to conceptualize legal updates in Indonesia in the governance and regulation of crypto assets in Indonesia. This type of research is normative juridical and is analyzed using qualitative data analysis, using legal comparisons from countries that already have crypto asset regulation first, then the Singapore state deserves to be used as a parameter to conceptualize legal updates in Indonesia in the governance and regulation of crypto assets in Indonesia.